Determination of Aflatoxin Levels in Consumed Hazelnut Cream in Istanbul, Turkey - VURAL, AYDIN; AYDIN, ALI; CAKMAK, OMER; EMIN ERKAN, M. (Asian Journal of Chemistry, 2010)
This study was carried out to determine aflatoxin levels in cacao hazelnut cream, which is a widely consumed product. First, a total of 182 cacao hazelnut cream samples were obtained randomly from retail points in Istanbul. Then they were analysed from January 2002 to December 2004 by ELISA technique for aflatoxin B1 and total aflatoksin. 51 Samples (28.02%) were investigated for total aflatoxin and 48 samples (26.37%) were investigated for AFB1 which were found to have exceeded the highest acceptable limits set down by the EU legal limit. The acceptable limits of the Turkish food codex are different from the EU. Out of 182 samples, only 10 (5.49 %) were found to have exceeded the limits for total aflatoxin and only five (2.74 %) were found to have exceeded the limits for aflatoxin AFB1 that were set down by the Turkish food codex.